2018
DOI: 10.3390/ijerph15122838
|View full text |Cite
|
Sign up to set email alerts
|

Mobile App-Based Health Promotion Programs: A Systematic Review of the Literature

Abstract: This study investigated the features and usefulness of mobile app-based health promotion programs for the general population. A comprehensive bibliographic search of studies on health promotion programs using mobile apps in peer-reviewed journals published in English up to November 2017 was performed using the PubMed, Embase, and CINAHL databases. The inclusion criteria were (1) randomized control trial designs; (2) assessed mobile app-based interventions to promote adult health conditions; 12 studies were ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(140 citation statements)
references
References 48 publications
2
124
0
14
Order By: Relevance
“…Sample sizes of the included research articles ranged from 26 to 16 948; sample sizes of the included evidence review articles ranged from 11 to 457 47. Twelve studies focused on males and females,20 36–42 44–46 48 one reported on females alone,18 one reported on all study population,49 one reported on employees50 and nine studies (systematic review) did not report study population 17 27 47 51–56. Seven of the studies reviewed were conducted in the community 39 41 44–46 48 56.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes of the included research articles ranged from 26 to 16 948; sample sizes of the included evidence review articles ranged from 11 to 457 47. Twelve studies focused on males and females,20 36–42 44–46 48 one reported on females alone,18 one reported on all study population,49 one reported on employees50 and nine studies (systematic review) did not report study population 17 27 47 51–56. Seven of the studies reviewed were conducted in the community 39 41 44–46 48 56.…”
Section: Resultsmentioning
confidence: 99%
“…), providing guidance and suggestions, and enhancing their determination to make changes when faced with challenges [ 11 ]. Studies have shown that health interventions in mobile applications are common and effective ways to improve health behaviors in the general population [ 12 ]. With the development of the mobile internet industry and the popularization of smart mobile devices, health-themed mobile apps have proliferated [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Focusing on physical activity, several scientific trials suggest that it can be effectively increased through smartphone interventions, which provide information and performance-related feedback, Open access monitor behaviour change, enable social networking and goal setting and include motivational messages or reminders. [12][13][14][15] Although the number of health apps on the market is already high (in 2016 >80 000 apps in categories 'health and fitness' and 'medicine' 16 ), and their potential in the health sector is promising, 9 17 18 only few of these apps use evidence-based content, practices and features. 19 Developing digital interventions that work equally well for people with different expectations, opportunities and cultural backgrounds is challenging.…”
Section: Introduction Backgroundmentioning
confidence: 99%